On the formalization of emergency action plans - Yalovets, A.L. (Інститут програмних систем НАН України, 2023)
The problem of formalization of action plans to counter emergency situations is being studied. It is noted that traditional action plans are text documents that are not suitable for solving the tasks of automating the management of emergency situations. A formal description of the state space is given and the expediency of using the state space graph to represent electronic action plans is substantiated. Based on the analysis of the internal structure of the process of countering an abstract emergency, a set of functional groups and their constituent operations are identified, using which an arbitrary action plan can be built. The identification of a set of types of parameters is carried out, through which the formalization of operations is provided. The advantages of using the proposed formalization of action plans for automating the processes of emergency response management are given.Prombles in programming 2023; 1: 38-47